The m6A Dynamics of Profilin in Neurogenesis - Rockwell, Antonio L.; Hongay, Cintia F. (Frontiers in Genetics, 2019)
Our understanding of the biological role of m6A, a ubiquitous non-editing RNA modification, has increased greatly since 2011. Work from several labs revealed that m6A methylation regulates several aspects of mRNA metabolism (Liu and Pan 2016, Cao et al. 2016). The “writer” protein METTL3, known as MT-A70 in humans, Dm Ime4 in flies, and MTA in plants, has the catalytic site of the METTL3/14/16 subunit of the methyltransferase complex that includes many other proteins. METTL3 is evolutionarily conserved and essential for development in multicellular organisms (Guela et al. 2015, Zhong et al. 2008, Hongay and Orr-Weaver 2011, Rockwell et al, 2019). However, until recently, no study has been able to provide a mechanism that explain the essentiality of METTL3. Here we focus on METTL3 and its likely conserved role in Profilin regulation in neurogenesis. However, this and many other subunits of the methyltransferase complex are starting to be identified in several developmental processes and disease (Chandola et al. 2015). A recent plethora of studies about the biological role of METTL3 and other components of the methyltransferase complex that erase (FTO) or recognize (YTH proteins) this modification on transcripts (Yang et al. 2018) shows that this RNA modification plays a variety of roles in many biological processes such as neurogenesis (Niu et al. 2014, Yoon et al. 2018, Spychala and Ruther, 2019). Our work in Drosophila shows that the ancient and evolutionarily conserved gene profilin (chic in Drosophila) is a target of the m6A writer (Rockwell and Hongay, under review). Here we discuss the implications of our study in Drosophila and how it unveils a conserved mechanism in support of the essential function of METTL3 in metazoan development. profilin (chic) is an essential gene of ancient evolutionary origins, present in sponges (Porifera), the oldest still extant metazoan phylum of the common metazoan ancestor Urmetazoa. We propose that the relationship between profilin and METTL3 is conserved in metazoans and it provides insights into possible regulatory roles of m6A modification of profilin transcripts in processes such as neurogenesis.